Sentinel Lymph Node Mapping: Current Applications and Future Perspectives in Gynecology Malignant Tumors - Wang, Tianyou; Xu, Yan; Shao, Wenyu; Wang, Chao (Frontiers in Medicine, 2022)
Sentinel lymph nodes (SLNs) are the first group of lymph nodes draining the lymph from the primary tumor, most affected when the tumor metastasizes, reflecting the state of lymph node involvement in the entire region. Sentinel lymph node mapping refers to intraoperative localization and biopsy of SLNs with specific tracers to assess lymph node metastases. It is widely used in a variety of tumor surgeries for its high sensitivity and high negative predictive value. In the evaluation of the status of lymph node metastases in gynecological malignancies, it has received increasingly more attention for its minor invasiveness, few complications, and high diagnosis rate. The NCCN guidelines provide an excellent introduction to the indications and methods of sentinel lymph node techniques in vulvar, cervical, and endometrial cancers, however, they provide little explanation about some specific issues. In this review, we summarize different dyes and injection methods, and discuss the indications of application and the clinical trials of sentinel lymph node mapping in gynecological malignant tumors, aiming to provide a reference for the rational application of sentinel techniques in gynecology malignant tumors before relevant guidelines are updated.